Effect of Leverage, Return on Assets (ROA), Inventory Intensity, and Company Size on Tax Aggressiveness - Subadriyah Subadriyah; Izzatur Rohmatun Na’imah; Moch Aminnudin (Jurnal Akuntansi dan Perpajakan, 2022)
This study entitled Effects of Leverage, Return On Assets (ROA), Inventory Intensity, and Company Size on Tax Aggressiveness (Empirical Study of Manufacturing Companies Registered on the IDX in 2018-2020) aims to examine and discuss the effects of leverage, return on assets (ROA) ), inventory intensity, and firm size on tax aggressiveness. This research is quantitative with secondary time series data. The sampling technique used purposive sampling technique. Data processing in this study uses Microsoft Excel and the SPSS program. the data analysis technique used is multiple regression analysis techniques, hypothesis testing, descriptive statistics, and classical assumption tests. The results of this study are the variables Leverage, ROA, and Company Size have no significant effect on tax aggressiveness, while the Inventory Intensity variable has a significant negative effect on tax aggressiveness.